KINERJA KARYAWAN BERDASARKAN PENGARUH EMPLOYEE ENGAGEMENT PADA KARYAWAN HOTEL RA PREMIERE SIMATUPANG JAKARTA - Aprilia, Lu'luwatin Rosdiana; Guntawan, Akhmad; Napitupulu, Gading Isaiah Bintang (Akademi Pariwisata NHI Bandung, 2024)
The purpose of this research is to find out the impact of employee engagement on the performance of employees of Hotel Ra Premiere Simatupang Jakarta. The population of this study is the entire staff of Hotel Ra Premiere Simatupang Jakarta with 54 respondents. Data collection techniques using google form questionnaires. This research method is quantitative descriptive analysis. The results showed a correlation number rotation of 0.272 means that the strength of the relationship between variables can be said to be sufficient. The direction of the coefficient number relationship to the result above is positive value of 0.272, then it can be meant that the increase in employee engagement then will improve the performance. It can be concluded that H0 is rejected, H1 is accepted then there is a significant influence and a very strong and directed relationship between employee engagement and the performance of employees of Hotel Ra Premiere Simatupang Jakarta.